Literatures in the Digital Era : Theory and Praxis. - Sanz, Amelia (Cambridge Scholars Pub., 2007)
The application of technology to information, communication, and culture has been through the history of humanity a key factor in social progress and well being. Literatures in the Digital Era: Theory and Praxis analyses in its twenty chapters the impacts of digital technology for the contemporary culture. The literary system is being powerfully affected in three aspects. In the first place, computer resources have been used to preserve and edit literary texts, associating to them graphical m ...